CRIMINAL RESPONSIBILITY FOR DOMESTIC VIOLENCE (Court Decision number 1945/Pid.Sus/2019/PN Mdn) - T. Riza Zarzani; Hendry Aspan; Andi Syah Putra Lubis (International Journal Reglement & Society (IJRS), 2021)
This study aims to determine criminal responsibility for domestic violence in court decision Number 1945 / Pid.Sus / 2019 / PN Mdn) and to find out the legal considerations of judges in imposing criminal sanctions against perpetrators of criminal acts of domestic violence committed by husbands against wives in Court decision Number . 1945 / Pid.Sus / 2019 / PN Mdn. The research used to answer the two things above is the decision literature research and the author takes the data obtained from the decision of the Medan District Court. The results of this study indicate that the application of material criminal law to criminal acts in the judge's decision in case No. 1945 / Pid.Sus / 2019 / PN Mdn. In accordance with the legislation in this matter regulated in law number 23 of 2004 concerning the elimination of domestic violence in imposing a criminal sentence, the judge has given considerations in accordance with the facts and it was revealed in the trial both from a material criminal and criminal perspective.